DEVELOPMENT OF A PUBLIC SERVICE MODEL THROUGH E - GOVERMENT IN LAMPUNG PROVINCE - Malik MALIK; Noning Verawati (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The nature of e - goverment, arguing the importance of e – Gorverment and process -based government information and communication technology, information and communication technology in the context of efficiency and effectiveness in the management of public affairs, among others, to the expansion of access to public information, development planning ,decision-making, and public services .Construction and development of e-government can not be separated from the use of information technology, in other words, before in the wake of e -government, the leader of the offices of government ( central and local ) must first know the business processes in depth, For more information technology implementation are not conceptual, so that the change must come from the leader who knows the process of change; thus, the information technology governance process becomes very important in a government organization .The gain from e -Government is not just a supply -line services but broader than that, because the performance of the public sector also contributes to economic and social progress of a country. In the era of globalization the implementation of e-Government is important because it has to modernize public administration in the world and also the relationship between the government or the state. In line with the objectives to be achieved sooner or later the government of Indonesia are required to implement the e -Government. At this time the e -Government is a necessity in order to create better public services.